Harry Potter and the goblet of fire - Rowling,J.K (London: Bloomsbury Publishing Plc, 2000)
Harry Potter and the Goblet of Fire is the fourth book in J.K. Rowling$1 (Bs Harry Potter series. The story begins with Harry and his friends, Ron and Hermione, attending the Quidditch World Cup, where they witness a violent attack by Death Eaters, followers of the dark wizard Voldemort. This event signals that Voldemort$1 (Bs return is imminent, though many in the wizarding world remain in denial about the danger. The central event of the book is the Triwizard Tournament, a magical competition held between three wizarding schools: Hogwarts, Beauxbatons, and Durmstrang. Harry is too young to participate, but his name is mysteriously drawn from the Goblet of Fire, an ancient magical artifact that selects the champions for the tournament. Despite not entering himself, Harry is forced to compete alongside the other champions: Cedric Diggory of Hogwarts, Viktor Krum of Durmstrang, and Fleur Delacour of Beauxbatons. As Harry faces a series of dangerous tasks in the tournament, he uncovers a sinister plot. The final task takes place in a maze, where Harry and Cedric Diggory reach the Triwizard Cup together, only to find that the cup is a Portkey that transports them to a graveyard. There, they encounter Lord Voldemort, who is fully revived using Harry's blood. Voldemort kills Cedric, and Harry barely escapes with his life, returning to Hogwarts with Cedric$1 (Bs body. The book ends with Harry revealing to the wizarding world that Voldemort has returned, but the Ministry of Magic and many others refuse to believe him. The dark times have officially begun, and the wizarding world is plunged into uncertainty and fear. The themes of friendship, bravery, and the clash between good and evil are central to the story, as Harry grows more aware of the threats surrounding him.s
Harry Potter and the Goblet of Fire is a significant and darker chapter in J.K. Rowling's Harry Potter series. The book marks a turning point in the overall arc, as the tone shifts from the more lighthearted adventures of the earlier books to a story filled with danger, intrigue, and the looming presence of evil. The book is notable for its introduction of the Triwizard Tournament, a thrilling magical competition that challenges Harry and his friends in ways they have never faced before. The central theme of the book revolves around the return of Lord Voldemort, whose resurrection in the final chapters signals the beginning of a new and darker era for the wizarding world. The story explores the concepts of destiny, courage, and the consequences of power, as Harry grapples with his role in the fight against Voldemort. The revelation that Voldemort is back, and that many in the wizarding world refuse to accept the truth, sets the stage for the increasing conflict that will unfold in the following books. Character development is a key aspect of The Goblet of Fire, with Harry becoming more mature as he faces both external dangers and personal loss. The book also delves deeper into the lives of secondary characters like Cedric Diggory, Viktor Krum, and Fleur Delacour, providing a broader look at the magical world beyond Hogwarts. The tragic death of Cedric Diggory serves as a sobering reminder of the real dangers of the wizarding world and the high stakes in the battle against dark forces. Overall, Harry Potter and the Goblet of Fire is a pivotal book that expands the scope of the series, setting up the final confrontations with Voldemort and establishing the darker, more perilous atmosphere that will dominate the series' climax. It is a blend of adventure, mystery, and emotional depth, showcasing the growth of its characters while foreshadowing the challenges ahead.
Keywords: Goblet of Fire; Triwizard Tournament